2018
DOI: 10.5194/amt-11-3661-2018
|View full text |Cite
|
Sign up to set email alerts
|

Homogenizing and estimating the uncertainty in NOAA's long-term vertical ozone profile records measured with the electrochemical concentration cell ozonesonde

Abstract: Abstract. NOAA's program of long-term monitoring of the vertical distribution of ozone with electrochemical concentration cell (ECC) ozonesondes has undergone a number of changes over the 50-year record. In order to produce a homogenous data set, these changes must be documented and, where necessary, appropriate corrections applied. This is the first comprehensive and consistent reprocessing of NOAA's ozonesonde data records that corrects for these changes using the rawest form of the data (cell current and pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 61 publications
4
90
0
Order By: Relevance
“…Vertical resolution is 250 m.10.1029/2018JD030098Journal of Geophysical Research: Atmospheres the measured signal. This is similar to the results inWitte et al (2018) that reported on ozone uncertainties in the reprocessed tropical Southern Hemisphere Additional Ozonesondes data set andSterling et al (2018) that presented uncertainty estimates for profiles at eight NOAA ozonesonde stations.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Vertical resolution is 250 m.10.1029/2018JD030098Journal of Geophysical Research: Atmospheres the measured signal. This is similar to the results inWitte et al (2018) that reported on ozone uncertainties in the reprocessed tropical Southern Hemisphere Additional Ozonesondes data set andSterling et al (2018) that presented uncertainty estimates for profiles at eight NOAA ozonesonde stations.…”
supporting
confidence: 91%
“…In the right panel of Figure 11b, the ratios of the WFF operational SST to the two profile types are closest to unity when the 2ZNOAA PCF is applied. These values have been recommended by Johnson et al (2002), applied to all NOAA-run station records, and validated by Sterling et al (2018) who recommends adding a 4% transfer function to the 2.0% NB ozone profiles when reprocessing. The agreement between sonde TCO and EP-TOMS overpasses are within 4% (mean absolute percentage differences with respect to the sondes) overall.…”
Section: 1029/2018jd030098mentioning
confidence: 99%
“…The ozonesonde package provided a high quality O 3 profile with an uncertainty in the 1 second data of ±1.5 ppb (Sterling et al, 2018). A comparison between the surface O 3 measurement obtained with the tethersonde and the O 3 value from the surface monitor operated by the CDPHE at the Ft. Collins West site shows agreement between the observations ( Figure S2) over the full range of mixing ratios sampled with a linear regression slope of 1.03 and R 2 of 0.99.…”
Section: Measurement Methodologiesmentioning
confidence: 99%
“…Because ozonesonde profiles are relied upon as the foundation for satellite O 3 retrievals and validation, we reexamine the agreement among sonde, satellite, and ground‐based TCO with two more years of data from the SHADOZ and NOAA networks to determine if the dropoffs reported in Thompson et al (2017) and Sterling et al (2018) persist. We also extend these analyses to the global network during the Aura satellite era of October 2004 to present.…”
Section: Background: the Ozonesonde Instrument And Data Quality Assurmentioning
confidence: 99%